The Impact of the Menstrual Cycle on Bargaining Behavior - Lina Lozano; Arno Riedl; Christina Rott (Institute of Labor Economics (IZA), 2024)
We investigate experimentally how the menstrual cycle affects bargaining behavior and bargaining outcomes of women. Female participants negotiate in an unstructured bilateral bargaining game with asymmetric information about the allocation of a surplus ('pie size'). We find that the menstrual cycle affects bargaining behavior and that the effects depend on the information players have. Players who are informed about the pie size are less compromising during ovulation and receive higher payoffs conditional on reaching an agreement. Uninformed players achieve higher final payoffs during ovulation, which is mainly driven by higher agreement rates.
Keywords: C78; C91; D87; J16; 330; bargaining; asymmetric information; menstrual cycle; biological factors